A Case Report on Prepubertal Vaginal Bleeding due to Leech Bite: History Is Very Important - S. M. Tajdit Rahman; Tasnim Shahriar; Adiba Tarannum; Md Abul Kasem; Tasnuva Akter (Case Reports in Obstetrics and Gynecology)
Though prepubertal vaginal bleeding is rare, it can create a dilemma for both physicians and parents. Prepubertal vaginal bleeding due to leech bite is even rarer and very difficult to diagnose without proper history. We report a case of a six-year-old girl presenting with vaginal bleeding and ultimately diagnosed as a case of vaginal bleeding due to leech bite. We described how focused history helped us in diagnosis and management of such case in rural areas with limited healthcare resources. A detailed history with a high index of suspicion and a thorough examination is essential to diagnose leech bite in the vagina.